Den kultur- och litteraturhistoriska gestalten i den lettiska novellen “Svētā Briģita” (“Heliga Birgitta”) av Jānis Ezeriņš - Orehovs, Ivars (Scandinavistica Vilnensis, 2019)
Cultural-historical and literary gestalt in the Latvian short story “Saint Birgitta” (“Heliga Birgitta”) by Jānis Ezeriņš The Latvian author Jānis Ezeriņš’s (1891–1924) literary heritage includes, among other texts, the collection of short stories Fantastiska novele un citas (Fantastic short story and others, 1923). The collection contains the short story “Svētā Briģita” (“Saint Birgitta”), in which the author has used the image of a saint, which is very well known in the history of culture, literature and religion. The image can be related both to Celtic mythology and the historical Swedish personality, who had been the founder of Vadstena monastery and a literary author herself (approx. 1303–1373). The aim of the article is to explore the function of the image in the prose text by the Latvian author Ezeriņš and its connections with the cultural and historical personality of St. Birgitta. It is not typical of Ezeriņš’s writings to make such an explicit and direct association with this kind of legendary phenomena, therefore the inclusion of the text in the collection may suggest a connection between St. Birgitta’s individual destiny and enduring human values. This writer’s choice can also be seen as his own claim to international recognition.